Functional Metal Oxide Nanostructures - Wu, Junqiao; Cao, Jinbo; Han, Wei-Qiang; Janotti, Anderson; Kim, Ho-Cheol (Springer Series in Materials Science, 2012)
Metal oxides and particularly their nanostructures have emerged as an important class of materials with a rich spectrum of properties and great potential for device applications. In this book, contributions from leading experts emphasize basic physical properties, synthesis and processing, and the latest applications in such areas as energy, catalysis and data storage.  Functional Metal Oxide Nanostructures is an essential reference for any materials scientist or engineer with an interest in metal oxides, and particularly in recent progress in defect physics, strain effects, solution-based synthesis, ionic conduction, and their applications. Addresses a hot area of electronic and magnetic materials Covers basic properties, synthesis, processing, and applications Focuses on nanoscale aspects of metal oxides Presents both recently developed theories and state-of-the-art applications.